1992
DOI: 10.1111/j.1365-2796.1992.tb00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐loading test, urinary albumin excretion and renal morphology in diagnosis of subclinical diabetic nephropathy

Abstract: The acute effects of protein loading (1.5 g kg-1) on glomerular filtration rate (GFR) and urinary albumin excretion (UAE) were investigated in 23 type-I diabetic patients with no clinical nephropathy, and in 7 healthy subjects (controls). The results were compared with renal morphology data. In controls and in 14 diabetic patients (group 1) GFR increased by 27 and 37%, respectively, corresponding to normal renal reserve, but in 9 patients (group 2) GFR decreased by 20%, indicating the absence of a renal reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…If lost, maximal GFR is established [18]. FRR is lost at early phases of type 1 DM [19]. At that stage the FRR and its relationship with urinary protein excretion and metabolic control are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…If lost, maximal GFR is established [18]. FRR is lost at early phases of type 1 DM [19]. At that stage the FRR and its relationship with urinary protein excretion and metabolic control are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This time point was prior to commencement of infusions and the finding is of considerable interest. Many factors other than BP have been associated with acute elevation in AER, including dietary protein (Shestakova et al 1992), posture, exercise (Gatling et al 1985 and diuresis (Viberti et al 1982). There was no relationship between urine volume and AER (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In the literature there is considerable inconsistency in reported RFR values in patients with Type 1 diabetes. In two studies where kidney biopsies were performed, negative RFR was found in patients with histological signs of glomerulosclerosis [1] and in patients with hilar glomerular lesions with expanded mesangium [2]. In both studies it was suggested that negative RFR precedes other subclinical manifestations of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 96%
“…Some patients with Type 1 diabetes mellitus have decreased renal functional reserve (RFR) before they develop incipient diabetic nephropathy [1,2] as characterised by microalbuminuria. At a very early stage of diabetic nephropathy, reduced endothelial sensitivity of renal afferent arterioles to nitric oxide occurs [3], possibly caused by reactive oxygen species [4,5].…”
Section: Introductionmentioning
confidence: 99%